2017
DOI: 10.1016/j.euf.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Xenografts of Human Clear Cell Renal Cell Carcinoma But Not Corresponding Cell Lines Recapitulate Clinical Response to Sunitinib: Feasibility of Using Biopsy Samples

Abstract: Background Parallel development of preclinical models that recapitulate treatment response observed in patients is central to the advancement of personalized medicine. Objective To evaluate the use of biopsy specimens to develop patient-derived xenografts and the use of corresponding cell lines from renal cell carcinoma (RCC) tumors for the assessment of histopathology, genomics, and treatment response. Design, setting, and participants A total of 74 tumor specimens from 66 patients with RCC were implanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…We have complied with all relevant ethical regulations. All surgical specimens were transported in RPMI medium or PBS on ice, washed with cold PBS, cut into small pieces (2 × 2 to 3 × 3 mm 3 ) and then implanted subcutaneously into one or two sides of the flank of 6-8-week-old male immunocompromised NOD-SCID IL2Rg −/− (NSG) mice (Jackson Laboratory) via a 4-5 mm skin incision over the mid-lumbar spine 46,47 . PDX from UCC11 was generated from a frozen cell pellet after a collagenbased digestion process.…”
Section: Methodsmentioning
confidence: 99%
“…We have complied with all relevant ethical regulations. All surgical specimens were transported in RPMI medium or PBS on ice, washed with cold PBS, cut into small pieces (2 × 2 to 3 × 3 mm 3 ) and then implanted subcutaneously into one or two sides of the flank of 6-8-week-old male immunocompromised NOD-SCID IL2Rg −/− (NSG) mice (Jackson Laboratory) via a 4-5 mm skin incision over the mid-lumbar spine 46,47 . PDX from UCC11 was generated from a frozen cell pellet after a collagenbased digestion process.…”
Section: Methodsmentioning
confidence: 99%
“…Various agents have been tested in the pre-clinical setting using PDX models to investigate tumor response. Importantly, it has been shown that PDX models for RCC can better correlate with clinical response to sunitinib than cancer cell lines [57]. In one of the largest studies to date, Sivavand et al performed validation of targeted therapies in 94 different RCC patient tumor samples, 35 of which yielded viable tumor xenografts, and 16 were able to be serially passed successfully.…”
Section: Correlation With Therapy Response and Chemosensitivitymentioning
confidence: 99%
“…Functional studies based on model systems to recapitulate genetic and phenotypic characteristics of the patient profile such as patient‐derived xenograft (PDX)/tissue grafts (TG), organoids and patient‐derived cultures that have recently been established from RCC . TG models were generally well‐characterized based on histology, gene expression and genomics, and are known to retain regional ITH .…”
mentioning
confidence: 99%
“…TG models were generally well‐characterized based on histology, gene expression and genomics, and are known to retain regional ITH . TG models only allow for small scale drug testing studies, however, may recapitulate the drug responsiveness in patients . A study on a single patient's PDX models derived from a primary and a lung metastatic sample showed noticeable variation in drug response profiles inferred from the single cell RNA‐sequencing (scRNA‐seq) of the paired samples, and underlined the impact of ITH in RCC .…”
mentioning
confidence: 99%